Bioreduction of Hydrogen Uranyl Phosphate: Mechanisms and U(IV) Products - Rui, Xue; Kwon, Man Jae; O'Loughlin, Edward J.; Dunham-Cheatham, Sarrah; Fein, Jeremy B.; Bunker, Bruce; Kemner, Kenneth M.; Boyanov, Maxim I. (American Chemical Society, 2013)
The mobility of uranium (U) in subsurface environments is controlled by interrelated adsorption, redox, and precipitation reactions. Previous work demonstrated the formation of nanorneter-sized hydrogen uranyl phosphate (abbreviated as HUP) crystals on the cell walls of Bacillus subtilis, a non-U-VI-reducing, Gram-positive bacterium. The current examined the reduction of this biogenic, cell-associated HUP mineral by three dissimilatory metal-reducing bacteria Anaeromyxobacter dehalogenans strain K, Geobacter sulfurreducals strain. PCA, and Shewanella putrefaciens strain CN-32, and compared it to the bioreduction of abiotically formed and freely suspended HUP of larger particle size. Uranium speciation hi the solid phase was followed over a 10- to 20-day reaction period by X-ray absorption fine structure spectroscopy (XCANES and EXAFS) an showed biogenic than with the abiotic material under the same experimental conditions. A greater extent of HUP reduction was observed varying extents of U-VI reduction to U-IV. The reduction extent of the same mass of HUP to U-IV was consistent the presence of bicarbonate in solution, whereas a decreased extent of HUP reduction was observed with the addition of, dissolved phosphate These results indicate that the extent of U-VI reduction is controlled by dissolution of the HUP h suggesting that the metal-reducing bacteria transfer electrons to the dissolved or bacterially adsorbed U-VI species formed after; HUP dissolution rather than to solid-phase U-VI in the HUP mineral. Interestingly, the bioreduced U-VI atoms were not immediately coordinated to other U-IV atoms (as in uraninite, UO2) but were similar in structure to the phosphate-complexed U-IV species found in ningyoite [CaU(PO4)(2)center dot H2O] This indicates a strong control by phosphate on the speciation of bioreduced U-IV, expressed as inhibition of the typical formation of uraninite under phosphate-free conditions.
Keywords: MICROBIAL REDUCTION; U(VI) REDUCTION; ANAEROMYXOBACTER-DEHALOGENANS; URANIUM IMMOBILIZATION; ELECTRON-TRANSFER; CITROBACTER SP; SHEWANELLA; SPECIATION; GROWTH; PHASE